TRIPS Application Binary Interface (ABI) Manual - Smith, Aaron; Burrill, Jim; McDonald, Robert; Yoder, Bill; Burger, Doug; Keckler, Stephen W.; McKinley, Kathryn (UT-Austin, Department of Computer Science, 2006)
This document specifies the TRIPS Application Binary Interface (ABI) Manual for the TRIPS architecture, a novel, scalable, and low power architecture for future technologies.
Proceedings of Fifteenth Conference on Uncertainty in Artificial Intelligence, ® Stockholm, Sweden